STRATEGI PENULISAN IKLAN HARIAN PARE POS DALAM MENINGKATKAN PELANGGAN DI KOTA PAREPARE - Iskandar Iskandar; Anna Yulianti; Uswatun hasanah (KOMUNIDA : Media Komunikasi dan Dakwah, 2016)
Strategy Copywriting daily Pare Post in Improving Pelangan of course very concerned about the quality and quantity of the writing of the ad itself, has even had a recipe or special tricks to improve customer, both in terms of layout, pattern, image, size, color, language and other things needed by the customer. This study used descriptive qualitative method, using mass media approach to literature analysis techniques, and interview. Research shows that: 1). Daily Ad Writing Strategies to Improve Customer Pos Pare is to improve the products every day, fix the issues, finding issues, what is most needed by the people and information that is most preferred. 2). factors affecting Copywriting is an ad published appear attractive depends on the creativity even have to have a prescription or special tricks to improve customer both in terms of layout, pattern, image, size, color, language and other things needed by the customer.